Adherence issues to antipsychotic medication in schizophrenia: results from a Hong Kong survey targeted for psychiatrists and case managers - Dr. , Ki-Yan Mak (International Journal of Psychosocial Rehabilitation, 2016)
Objective: The overall level of adherence of Hong Kong patients with schizophrenia is relatively unknown, and this report therefore aims to investigate the attitude of local patients towards antipsychotics, to hopefully assist future development of potential strategies to address adherence problems. Methods: A survey consisting of adherence-related questions in schizophrenia was given to 71 psychiatrists and 143 case managers in Hong Kong. Survey results were summarised descriptively, and percentages for each multiple choice answer picked for each question were calculated. Results: Over half of the surveyees estimated that their patients were either partially or non-adherent with their anti- psychotic medication during the past month. The three major barriers to patient recovery and improved functioning were “medication non-adherence” (93%), followed by “loss of insight into illness” (85%), and “lack of integrated psychosocial support” (45%). A large proportion of patients did not understand the risk of relapse due to non-adherence and showed lack of insight into illness. Conclusion: Our findings provide a glimpse of the adherence issues and perceptions of local healthcare providers regard- ing medication taking behaviours of local patients with schizophrenia. Further studies are required to examine the factors behind treatment non-adherence.